Transition States in Single-Case Experimental Designs: A Retrospective Consecutive-Controlled Case Series Investigation. Issue 1 (January 2023) - Laureano, Brianna; Falligant, John Michael
Behavioral interventions to decrease problem behavior often involve the use of single-case experimental designs in which an individual's responding during a treatment condition is compared to responding during a control or baseline condition. It is possible that during the initial introduction of treatment, problem behavior continues to occur at baseline rates before behavior reduction is observed; this phenomenon is called a transition state. Evaluated the prevalence of transition states in the Journal of Applied Behavior Analysis and found that they occurred within 5.3% of the published literature. The current study replicated and extended Brogan et al. by evaluating the prevalence of transition states in unpublished clinical data of patients admitted to an inpatient hospital for the treatment of severe problem behavior. Using a retrospective consecutive-controlled case series, transition states were observed in 3% of cases for an average duration of 4.8 sessions. We discuss factors that may affect transitional behavior between phases and relevant implications for practice and research.